Implementasi Mesin Produksi Pelet Apung untuk Mendukung Kemandirian Pakan Kelompok Budidaya Ikan di Desa Karangasem, Bulu, Sukoharjo - Rian Prasetyo; Ainur Komariah; Achmad Mufid Marzuqi (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
The high cost of fish feed has become the main problem in fish farming in Karangasem Village, Bulu District, Sukoharjo Regency. The “GP” Fish Farmers Group has long depended on commercial feed, which continues to increase in price and reduce profit margins. Meanwhile, local raw materials such as tofu waste, rice bran, and fish meal are abundantly available but have not been fully utilized due to the lack of processing technology. This community service program was carried out to implement a floating pellet machine as a solution to support feed self-sufficiency. The method consisted of three stages: preparation, implementation, and monitoring-evaluation. The preparation stage involved identifying partner needs and designing the pellet machine. The implementation stage included discussions, machine assembly, and feed production trials using local ingredients. Monitoring and evaluation were conducted through technical assistance and interviews with the group. The results indicate that the partners were able to operate the machine independently and produce floating pellets suitable for gourami and catfish farming. The use of this machine has proven effective in reducing feed costs, improving farming efficiency, and strengthening the group’s economic independence.